PENGARUH STRATEGI POW+TREE TERHADAP KEMAMPUAN MENULIS PARAGRAF - Hidayatul Dina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
POW+TREE Strategy helps students write and develop ideas easily. However, not all of the students were able to write text types. The objective of this research to find out whether there is a significant effect of POW+TREE Strategy towards students’ writing ability of the students at SDN 169 Pekanbaru. This research was experimental research which had two classes experimental class and control class. This research focused on writing the next paragraph. The researcher applied the POW+TREE Strategy in the experimental class. While in control class the researcher did not apply the strategy. Further, the researchers gave two tests for the students, pre and post-test. Then, the researchers gave pretest before giving the treatment. And then, the researchers gave post-test after applied the treatment in the experimental class. The result of students’ score in the control class was, the researchers got a mean score of pre-test was 46.17. While, in post-test, the researcher got a mean score was 60.67. However, the researcher got the students’ mean score in the experimental class was 49.5. After the researchers applied the POW+TREE Strategy, the mean score of students become 65.50. Thus, there was an increase in students score after using the strategy. Based on the researchers’ analysis by using SPSS 22.0 program by using Kolmogorov-Smirnov, the researchers got a significant test was 0.05. it was same as the standard significant. In brief, there was a significant effect of POW+TREE Strategy towards students’ writing ability of the students at SDN 169 Pekanbaru.